Together With Families. The Salerno System through Listening, Co-Planning, Shared Social Responsibilities and the Perspective of Childhood Pole - Trapanese, Rossella; Del Forno, Massimo (Italian Sociological Review, 2022)
The pandemic has defined a passage of time, requiring a reflection on the disparities regarding territorial guarantees and the opportunities offered to citizens in the different stages of life. Among these, support in the childhood field is one of the strategic guidelines of the Italian challenge to relaunch the country. The essay, after presenting statistical data and reconstructing the regulatory evolution of the sector, addresses the analysis of 0-3 years old services in the territorial context of the municipality of Salerno, retracing the phases of the pre, during and post lockdown periods, analyzed through three specific research activities. The aim is to understand over time, which relational dynamics have developed, from the network in the area to meet the needs of children and their parents and what changes have been made to the services. And finally, what assesment has been given to the processes activated and what prospects open up in the light of the innovations introduced. The underlying assumption is that listening, empowerment and participatory processes can be the “conditions of possibility” to increase citizens’ confidence and the effectiveness of services, by initiating co-planning and co-implementation which respond better to the needs of families and, more generally, the challenge of territorial relaunch posed by the post-pandemic phase, which can be achieved only through more shared responsibilities.